2015
DOI: 10.1002/bit.25623
|View full text |Cite
|
Sign up to set email alerts
|

Enforced ATP futile cycling increases specific productivity and yield of anaerobic lactate production in Escherichia coli

Abstract: The manipulation of cofactor pools such as ATP or NAD(P)H has for long been recognized as key targets for metabolic engineering of microorganisms to improve yields and productivities of biotechnological processes. Several works in the past have shown that enforcing ATP futile cycling may enhance the synthesis of certain products under aerobic conditions. However, case studies demonstrating that ATP wasting may also have beneficial effects for anaerobic production processes are scarce. Taking lactic acid as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 25 publications
(34 reference statements)
6
60
0
Order By: Relevance
“…The excretion rate of fermentation products could also be increased by implementing ATP futile cycles aerobically [17,20,21]. For anaerobic conditions, only recently an elevated specific lactate production rate was observed by implementing an ATP futile cycle between pyruvate and phosphoenolpyruvate (PEP) through overexpression of the PEP synthase [22]. In concordance with other experimental results, this study also reported a decreased growth rate and significantly increased glucose uptake rate.…”
Section: Experimental Studies Manipulating the Atp Pool In Escherichisupporting
confidence: 79%
See 1 more Smart Citation
“…The excretion rate of fermentation products could also be increased by implementing ATP futile cycles aerobically [17,20,21]. For anaerobic conditions, only recently an elevated specific lactate production rate was observed by implementing an ATP futile cycle between pyruvate and phosphoenolpyruvate (PEP) through overexpression of the PEP synthase [22]. In concordance with other experimental results, this study also reported a decreased growth rate and significantly increased glucose uptake rate.…”
Section: Experimental Studies Manipulating the Atp Pool In Escherichisupporting
confidence: 79%
“…In such a scenario, in addition to the product yield and specific productivity, even the volumetric productivity could be increased. However, the observed increased substrate uptake rates [22] upon ATP wasting could not completely restore the original growth rate.…”
Section: Effects Of Atp Wasting On Process Parametersmentioning
confidence: 63%
“…As described previously, the AAC strategies are able to increase the specific productivity and yield for chemical production (Hädicke et al 2015); however, there are no reports showing that the volumetric productivity and yield can be improved simultaneously, and this is something we have achieved in this study by fine-tuning the expression of the F 1 -ATPase. We selected acetoin production for this investigation as acetoin formation generates ATP (2 mol ATP per mol acetoin formed), and it is essential for the strategy to work that the biosynthetic pathway involved generates surplus ATP.…”
Section: Discussionmentioning
confidence: 87%
“…Patnaik et al was able to stimulate the glycolytic flux in Escherichia coli under aerobic conditions, by overexpressing phosphoenolpyruvate synthase, which generated an ATP consuming futile cycle (Patnaik et al 1992). Hädicke et al used the same futile cycle for improving lactate production in E. coli under anaerobic conditions (Hädicke et al 2015). Koebmann et al took a different approach and expressed the F 1 -ATPase in the cytoplasm of E. coli and achieved the same effect, i.e., stimulation of glycolytic flux (Koebmann et al 2002b).…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, cells have to be forced to high glucose uptake rates even when they are not growing. As the ATP maintenance demand seems to be the main driving force for itaconic acid production in this phase, ATP‐wasting strategies (Hädicke, Bettenbrock, & Klamt, 2015; Hädicke and Klamt, 2015; Liu, Kandasamy, Wurtz, Jensen, & Solem, 2016) could be used to increase substrate turnover. Besides, manipulation of regulatory networks (Michalowski, Siemann‐Herzberg, & Takors, 2017) and certain nutrient limitations (Chubukov & Sauer, 2014) might further increase uptake rates.…”
Section: Resultsmentioning
confidence: 99%